1998
DOI: 10.1095/biolreprod58.1.116
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-Independent Regulation of Steroidogenesis in the Fetal Rat Testis1

Abstract: 1) Pituitary LH cannot be the initial stimulus for fetal testicular steroidogenesis. 2) Some paracrine factor(s) probably turn on and maintain early fetal testicular steroidogenesis before the later onset of LH secretion, although a constitutive component in the onset of steroidogenesis is also possible. 3) VIP and PACAP-27 are likely candidates for a paracrine stimulus of the fetal testis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 48 publications
2
93
0
3
Order By: Relevance
“…Our findings that PACAP is required for testosterone biosynthesis in vivo are consistent with previous in vitro studies in which PACAP was shown to stimulate testosterone secretion by embryonic and adult Leydig cells (20)(21)(22)29). Nevertheless, the low testosterone concentration in PACAP Ϫ/Ϫ mice does not affect the fertility of these animals that routinely breed in our facility.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings that PACAP is required for testosterone biosynthesis in vivo are consistent with previous in vitro studies in which PACAP was shown to stimulate testosterone secretion by embryonic and adult Leydig cells (20)(21)(22)29). Nevertheless, the low testosterone concentration in PACAP Ϫ/Ϫ mice does not affect the fertility of these animals that routinely breed in our facility.…”
Section: Discussionsupporting
confidence: 92%
“…It has been suggested that steroidogenesis itself and, more specifically, the microsomal P450c17 protein (5, 6) participates in the age-induced testis degradation by generating ROS, which have been shown to negatively impact on steroidogenesis in vitro (28) and have been proposed as responsible for the age-related senescence of the Leydig cells in vivo (14). The neuropeptide PACAP has been implicated in regulation of testosterone level in cultured Leydig cells (20)(21)(22)29). It has also been shown to potentially enhance the release of LH in vivo (18).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to humans, the mouse genome does not contain a gene encoding chorionic gonadotroin. In contrast to humans, the sexual differentiation of male mice in utero can occur totally independent of LH/LHR action (El-Gehani et al, 1998;Pakarinen et al, 2002).…”
Section: Introductionmentioning
confidence: 88%
“…The adult Leydig cells are completely dependent on LH support for both development and adult function; in the absence of LH few adult Leydig cells develop and circulating testosterone levels are barely detectable (O'Shaughnessy et al ., 1998; Baker & O'Shaughnessy, 2001; Lei et al ., 2001; Zhang et al ., 2001). In contrast, the foetal Leydig cells in rodents appear to function largely independently of hormonal support (El Gehani et al ., 1998; O'Shaughnessy et al ., 1998; Baker et al ., 1999; Lei et al ., 2001; Zhang et al ., 2006) although in other species LH (or hCG in humans) is required for foetal androgen production (O'Shaughnessy & Fowler, 2011). …”
Section: Leydig Cellsmentioning
confidence: 99%